OPTIMASI PROSES BLEACHING TANDAN KOSONG KELAPA SAWIT DENGAN RESPON ALKALI PEROKSIDA DAN SUHU - Khairiyah, Nurul; Permata, Deivy Andhika; Azrifirwan (Jurnal Teknologi Pertanian Andalas, 2025)
Empty oil palm fruit bunches (OPEFB) are an agro-industrial waste with a high cellulose content, but lignin is a constraint in their utilization. This study aims to examine the optimal alkali peroxide concentration and temperature in the OPEFB bleaching process. This study uses Response Surface Methodology (RSM) with Central Composite Design (CCD). The research factor include the concentration of NaOH, H₂O₂, and bleaching temperature, with responses of yield, water content, ash content, whiteness degree, and Kappa number. The results showed that the research factors influenced the observed response. RSM provided an optimum combination solution at a concentration of 9.35% NaOH, 31.50% H₂O₂, and a temperature of 84.35°C, with a desirability of 0.789.